(untitled) (Journal of Atomic and Molecular Sciences, 2013)
The structural, stability and elastic property of single-walled ZnS nanotubes (SW-ZnS NTs) with armchair and zigzag forms were investigated using first-principles approaches. We have investigated a size dependence of stability and elastic modulus in SW-ZnS NTs. It is found that both the stability and the Young’s modulus are decrease dramatically with increasing diameter and proportional to the Zn-S bond length.